CHALLENGES IN INTERPRETATION OF BALLISTIC INJURIES – A LEGAL PROSPECTIVE (Journal of Forensic Medicine & Toxicology, 2024)
The terminology forensic ballistics was first given by colonel Calvin Goddard. The word “ballistics” defines the science of projectiles. The Forensic Ballistics is the application of the knowledge of firearms, powders and bullets to judicial problems. Forensic Ballistics provides scientific evidence which helps in court of law. Ballistic data have been of service to our judiciary, gives idea as to what can be expected from a scientific examination of the firearm exhibits which are so often introduced in our courts. It is always necessary to be kept in mind the sections which comes under the Arm Act. Firearm identification, Bullet identification, Cartridge identification is very important, as principle of identification says “Every Contact Leaves a Trace” . Various Methods are available which differentiate between bullet and cartridge case comparison and the challenges faced at interpretation of ballistic injuries.
Keywords: Forensic Ballistics; Court of Law; Firearm; Identification; Arm Act